COLLABORATIVE GOVERNANCE STRATEGIES FOR NAVIGATING THE DEMOGRAPHIC BONUS: EVIDENCE FROM THE BOS MUDA PROGRAM IN MAGELANG CITY - Huda, Usman; Sinuraya, Suci Iriani; Winanta, Rizza Arge; Noormansyah, Reza (Journal of Social Politics and Governance (JSPG), 2025)
Magelang City is currently undergoing a demographic bonus phase, marked by a large, productive workforce. However, this potential has not yet driven significant economic growth. High youth unemployment and a limited number of young entrepreneurs remain key barriers to the region’s progress. This study explores how collaborative governance helps address these challenges through the BOS Muda Program in Magelang City. Using a qualitative method with a case study approach, the research applies Ansell and Gash’s (2008) collaborative governance theory, focusing on the pentahelix collaboration model. The findings show that collaborative governance has been effectively implemented in the BOS Muda Program. The program enabled participants to start businesses and hire employees, offering a practical solution for managing demographic bonus challenges. Despite these successes, the study also highlights several barriers. Maintaining consistent participation in face-to-face dialogue sessions was difficult due to conflicting departmental schedules. Additionally, some participants dropped out because of limited capital and the program's long training period. Interestingly, the program also involved participants who were already entrepreneurs, which, although unintended, contributed positively to the program’s outcomes. Overall, the study underlines the importance of strong multi-stakeholder collaboration in ensuring that demographic advantages translate into economic opportunities for the region.